Improved hybrid methods in solving single variable nonlinear algebraic equations / Nor Hanim Abd Rahman - Abd Rahman, Nor Hanim (Institute of Graduate Studies, UiTM, 2017)
Nonlinear problem is one of the most frequently occurring problems in scientific works especially in science and engineering applications. Amongst the most popular schemes are the Newton’s method and homotopy perturbation method. However, the duration to converge are heavily depends on how close the guess value is to the real root/s and the rate of convergence for Newton’s method is only order-2 and its efficiency index is only ≈ 1.41421. Secondly, some of the methods utilized successive approximation procedure to ensure every step of computing will converge to the desired root and one of the most common problems is the improper initial values for the iterative methods. Thus, this particular research aims to develop an improved numerical solution for solving nonlinear equations by using hybrid concept and higher order correctional terms. Higher order successive approximations are applied and evaluated to ensure it converges to the desired root/s more effectively..